Optimising digestate fertilisation for onion (Allium cepa L.) production under semi-arid conditions: Effects on soil fertility, crop performance and yield - Jalal, H; Salah, EL; Rachid, L; Fouad, R (Plant Science Today, 2026)
Onion (Allium cepa L.) farming in the Fez–Meknes region is heavily dependent on mineral fertilisers, yet prolonged use has weakened soil quality and nutrient efficiency. This study assessed whether anaerobic digestate (AD) could provide a viable alternative in semi-arid conditions and regions. The experiment took place in the field during the 2023–2024 season in a randomised complete block design, comparing six treatments: an unfertilized control, local recommended mineral fertilisation (10:30:10) and digestate applied at (10, 20, 30 and 40 dry weight (DW) t/ha). Soil characteristics, plant growth traits, biomass and yield were recorded at 30, 60 and 90 days after planting and at harvest. Differences among treatments were statistically significant according to ANOVA (P < 0.05). Digestate doses shifted soil fertility indicators. Organic matter rose by +21.1 %, available phosphorus by +64.1 % and mineral nitrogen by +483 %, while electrical conductivity increased with higher application rates. Onion plants also responded strongly. At 60 days after planting, the (40 DW t/ha) dose raised plant height by +38.8 % and by 90 days after planting, the same treatment sharply increased the leaf number (+94.5 %). Biomass patterns followed a similar trend, with bulb fresh weight at 60 days after planting climbing by +140.8 % under (40 DW t/ha). Yield gains were clear across all digestate levels: the control treatment produced 54.64 t/ha, the recommended mineral fertilization reached (73.69 t/ha) and the highest value appeared at (30 DW t/ha) with 75.25 t/ha (+37.8 % above the control treatment), slightly exceeding both the recommended mineral fertilization and the (40 DW t/ha) treatment.